Influence of specimen geometry on temperature increase during ultrasonic fatigue testing - Bach, Jochen; Höppel, Heinz Werner; Bitzek, Erik; Göken, Mathias (Ultrasonics, 2013)
During the last decades the interest in fatigue properties of materials subjected to more than 107 cycles has strongly increased. To reach such high numbers of cycles the use of ultrasonic fatigue testing systems is a well-established method due to their very high fatigue frequencies. However particular considerations about the specimen design have to be made for ultrasonic fatigue testing. In order to investigate the influence of the specimen design on the fatigue behavior in more detail, two different gauge lengths were chosen. The influence of specimen design was found to be very prominent on the characteristic frequencies which are used for operating ultrasonic fatigue testing systems. As it is already known, with increasing specimen mass the characteristic frequency decreases. Also the amplitude has an influence on the characteristic frequency during an ultrasonic fatigue test. With increasing test amplitude micro-plasticity becomes more pronounced which leads also to a decrease in frequency. Most prominent, a distinct influence of the specimen geometry on the temperature increase during cycling was found. Specimens with a shorter gauge length showed a higher increase in temperature then specimens with the longer gauge length. It is suggested that these observations are caused by an easier and more equal distribution of heat in the specimens with the longer gauge length design. The influence of specimen shape was accomplished by simulation using a finite element method. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Very high cycle fatigue; Ultrasonic fatigue; Ultrasonic fatigue specimen design; Characteristic frequency